2019
DOI: 10.1111/codi.14831
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of and risk factors for lymphocele formation after lateral pelvic lymph node dissection for rectal cancer: a retrospective study

Abstract: Aim Pelvic lymphocele is a common complication that develops after pelvic lymph node dissection. The incidence of pelvic lymphocele formation has been reported to be 10.5-51% after gynaecological or urological procedures. However, no evidence has been reported thus far with regard to the development of pelvic lymphocele following lateral pelvic lymph node dissection (LPND) for low rectal cancer. The aim of this study was to investigate the incidence of and risk factors for lymphocele formation after LPND for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 38 publications
1
5
1
Order By: Relevance
“…Lymphocele sometimes causes severe complications when it compresses adjacent structures, including the urinary tract, vascular anatomy, or bowel. 15,16,27,28 Consistent with previous studies, 15 more than half of the patients (n = 18) in the present study were asymptomatic and diagnosed by routine follow-up CT scans. Among them, the lymphocele was spontaneously resolved in 13 patients and 5 patients still had the lymphocele at the last follow-up.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Lymphocele sometimes causes severe complications when it compresses adjacent structures, including the urinary tract, vascular anatomy, or bowel. 15,16,27,28 Consistent with previous studies, 15 more than half of the patients (n = 18) in the present study were asymptomatic and diagnosed by routine follow-up CT scans. Among them, the lymphocele was spontaneously resolved in 13 patients and 5 patients still had the lymphocele at the last follow-up.…”
Section: Discussionsupporting
confidence: 92%
“…It usually develops within 3 to 8 weeks after surgery, but in some patients, it may occur 1 year after surgery. 15,16 The clinical manifestation is heterogeneous; in most patients, it was reported as clinically asymptomatic and was diagnosed during routine checkups. Lymphocele sometimes causes severe complications when it compresses adjacent structures, including the urinary tract, vascular anatomy, or bowel.…”
Section: Discussionmentioning
confidence: 99%
“…LLND was not a risk factor for chylous ascites in the current work, and despite many reports of lymphatic leakage after LLND, 26,27 few describe chylous ascites. One previous study demonstrated that triglycerides in the diet are absorbed into the lymphatic system as chylomicrons following conversion into monoglycerides and fatty acids in the small intestine.…”
Section: Discussioncontrasting
confidence: 49%
“…63,78,79 Incidence of symptomatic lymphoceles was, however, correlated to the number of lymph nodes removed from patients with prostate cancer, which was also seen in patients with rectal cancer and gynecologic cancer undergoing pelvic lymph node dissection. 77,79,80 Factors associated with the development of lymphoceles in patients who underwent renal transplantation include the use of mammalian target of rapamycin (mTOR) inhibitors, laparoscopic procurement of graft, and the presence of more than one renal artery. 81…”
Section: Etiologymentioning
confidence: 99%